Cardiotoxicity mechanisms of antitumor therapy with immune checkpoint inhibitors: new achievements - L. D. Khidirova; A. E. Latsvieva; A. V. Vederin (Столичная издательская компания, 2024)
The immune checkpoint inhibitors (ICTs) emergence has opened up new perspectives in cancer immunotherapy. Nevertheless, serious, including life-threatening conditions caused by ICT cardiotoxic effects pose a number of obstacles to clinical specialists. The lack of knowledge about pathophysiology of cardiovascular adverse events in the treatment of ICT tumors is one of the reasons why oncological specialists seek help from cardiologists. Some works consider the mechanisms of individual complications development, but the number of works that would systematize and summarize descriptions of all the most significant ICT inhibitor therapy complications is small. In this regard, a literature review on the use of ICT inhibitors was conducted with a search in PubMed, Embase, Web of Science, e-L ibrary, Google Scholar. The purpose was to analyze the accumulated data on the mechanisms of ICT therapy complications development; Preference was given to systematic reviews, randomized clinical trials, which would be supplemented by separate cohort studies and descriptions of some experiments. Thus, it was determined that the ICT inhibitors cardiotoxicity can affect any part of the cardiovascular system, causing changes in both inflammatory and non-inflammatory etiology. Understanding their mechanisms increases the ability of specialists to form an effective treatment strategy while minimizing the risk of complications. Although a lot of theoretical, experimental and clinical empirical data on the side effects of this class of anticancer drugs have been accumulated in oncological practice, the ICT inhibitors cardiotoxicity is a problem requiring further research.